Alginate-Based Edible Coatings Enriched with Cinnamon Essential Oil Extend Storability and Maintain the Quality of Strawberries under Tropical Condition - Siburian, Putri Wahyuni; Falah, Moh. Affan Fajar; Mangunwikarta, Jumeri (Universitas Muhammadiyah Yogyakarta, 2021)
Strawberries are often transported and sold without temperature control, which causes huge losses due to rapid decay and quality deterioration. In this study, the effectiveness of edible coatings using alginate and enriched with an antibacterial agent (cinnamaldehyde from Cinnamomum burmannii essential oil), to maintain the quality and shelf life of strawberry was examined. Alginate coatings were prepared by dissolving 2%(w/v) sodium alginate, 0.5%(v/v) glycerol, 0.1%(w/v) CMC, and 0.5% (w/v) stearic acid, while antimicrobial agent was prepared by homogenizing 0.5%(v/v) cinnamon essential oil and 0.2%(v/v) Tween 20. Physicochemical and biochemical attributes [weight loss, firmness, color (L*, a*, b*), soluble solids content, vitamin C loss, acidity level, odor, total yeast and molds, and total mesophilic microorganisms were analyzed during storage under tropical conditions at 27Â±2Â°C. Statistical analysis was performed using ANOVA followed by a Tukey test. The inhibitory activity of antimicrobial agent was evaluated using the disc diffusion method. An alginate-based coatings enriched with Cinnamomum burmannii essential oil (AL+CBEO) was effective in maintaining physicochemical quality attributes and reducing the number of spoilage microorganisms, while alginate coatings alone (AL) found to be optimal for vitamin C loss prevention and additionally exhibited a more desirable odor. Overall, strawberry stored under tropical conditions appeared to be better preserved by alginate-based coatings enriched with cinnamon essential oil.Â